A TMS study on the contribution of visual area V5 to the perception of implied motion in art and its appreciation. Issue 1 (2nd January 2017) - Cattaneo, Zaira; Schiavi, Susanna; Silvanto, Juha; Nadal, Marcos
ABSTRACT: Over the last decade, researchers have sought to understand the brain mechanisms involved in the appreciation of art. Previous studies reported an increased activity in sensory processing regions for artworks that participants find more appealing. Here we investigated the intriguing possibility that activity in cortical area V5—a region in the occipital cortex mediating physical and implied motion detection—is related not only to the generation of a sense of motion from visual cues used in artworks, but also to the appreciation of those artworks. Art-naïve participants viewed a series of paintings and quickly judged whether or not the paintings conveyed a sense of motion, and whether or not they liked them. Triple-pulse TMS applied over V5 while viewing the paintings significantly decreased the perceived sense of motion, and also significantly reduced liking of abstract (but not representational) paintings. Our data demonstrate that V5 is involved in extracting motion information even when the objects whose motion is implied are pictorial representations (as opposed to photographs or film frames), and even in the absence of any figurative content. Moreover, our study suggests that, in the case of untrained people, V5 activity plays a causal role in the appreciation of abstract but not of representational art.